Contemplation and Organization Studies: Why contemplative activities are so crucial for our academic lives. Issue 10 (October 2019) - Bartunek, Jean M.
Contemporary emphases on calculating the impact of our scholarship can be deadening if they lead us to refrain from contemplation. Thus, in this essay, I show the importance of contemplation and what contemplative dimensions of our scholarship might include. Based on four lines from the poem "Sometimes" by the poet Mary Oliver, I summarize ways that many activities carried out by organizational scholars embody Oliver's "Instructions for living a life, " which consist solely of "Pay attention. Be astonished. Tell about it." My summary shows some of the range of contemplative activities within our field, as well as integral relationships between contemplation and compassion. I conclude by highlighting the importance of the roles such activities play in our experiences of academic life and in our developmental journeys as scholars.